Kawin Beda Agama: Tentang Konstitusional dan Nilai Pancasila di Indonesia : Interfaith Marriage: About Constitutional and Pancasila Values in Indonesia - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Khurin Nihayati; Hawa Habibah Rohayati; Yowanda Eca Aulia Gunawan (Litera Academica Publishing, 2025)
In Indonesia, interfaith marriage is often discussed in society and becomes a problem in legal and social contexts. Indonesia is a country with many different religions, with Pancasila as the country's foundation and values of tolerance and pluralism. However, regulations on interfaith marriage often lead to conflicts between state law and religious rules. The method used in this journal is a statutory approach and a case approach and also uses normative research. Analysis of Religious Marriage Regulations in Indonesia, Challenges in Legal Implementation, Recommendations for Legal Reform. The conclusion of this study shows that the legal regulation of interfaith marriage in Indonesia as stipulated in Law No. 1 of 1974, is still not fully in line with the principles of the constitution and the values of Pancasila which emphasise pluralism and freedom of religion. Simplification of legal procedures: It is recommended that administrative procedures related to interfaith marriage such as marriage registration and family status determination be simplified so that married couples can obtain their citizenship rights without obstacles.